Chondroitinase and growth factors enhance activation and oligodendrocyte differentiation of endogenous neural precursor cells after spinal cord injury. - Soheila Karimi-Abdolrezaee (Public Library of Science (PLoS), 2012)
The adult spinal cord harbours a population of multipotent neural precursor cells (NPCs) with the ability to replace oligodendrocytes. However, despite this capacity, proliferation and endogenous remyelination is severely limited after spinal cord injury (SCI). In the post-traumatic microenvironment following SCI, endogenous spinal NPCs mainly differentiate into astrocytes which could contribute to astrogliosis that exacerbate the outcomes of SCI. These findings emphasize a key role for the post-SCI niche in modulating the behaviour of spinal NPCs after SCI. We recently reported that chondroitin sulphate proteoglycans (CSPGs) in the glial scar restrict the outcomes of NPC transplantation in SCI by reducing the survival, migration and integration of engrafted NPCs within the injured spinal cord. These inhibitory effects were attenuated by administration of chondroitinase (ChABC) prior to NPC transplantation. Here, in a rat model of compressive SCI, we show that perturbing CSPGs by ChABC in combination with sustained infusion of growth factors (EGF, bFGF and PDGF-AA) optimize the activation and oligodendroglial differentiation of spinal NPCs after injury. Four days following SCI, we intrathecally delivered ChABC and/or GFs for seven days. We performed BrdU incorporation to label proliferating cells during the treatment period after SCI. This strategy increased the proliferation of spinal NPCs, reduced the generation of new astrocytes and promoted their differentiation along an oligodendroglial lineage, a prerequisite for remyelination. Furthermore, ChABC and GF treatments enhanced the response of non-neural cells by increasing the generation of new vascular endothelial cells and decreasing the number of proliferating macrophages/microglia after SCI. In conclusions, our data strongly suggest that optimization of the behaviour of endogenous spinal NPCs after SCI is critical not only to promote endogenous oligodendrocyte replacement, but also to reverse the otherwise detrimental effects of their activation into astrocytes which could negatively influence the repair process after SCI.